2018
DOI: 10.1029/2018jd028365
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Required in Measurements of Refractive Index and Hygroscopic Response to Reduce Uncertainties in Estimates of Aerosol Radiative Forcing Efficiency

Abstract: The magnitude of aerosol radiative forcing resulting from the scattering and absorption of radiation is still uncertain. Sources of uncertainty include the physical and optical properties of aerosol, reflected in uncertainties in real and imaginary refractive indices (n and k) and relative humidity (RH). The effect of RH on the geometrical size of aerosol particles is often reported as a hygroscopic kappa parameter (κ). The objective of this study is to explore the sensitivity of radiative forcing efficiency (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 64 publications
1
33
0
Order By: Relevance
“…More generally, the predictions of these properties must be robust in order to relate mass concentrations to size distributions of ambient aerosols and to calculate the radiative impacts of atmospheric aerosols. 45,46 Thus, a rigorous assessment of estimation methods based on solutions of known properties is of considerable value.…”
Section: Extension and Validation Of The Molar Refraction Mixing Rulementioning
confidence: 99%
See 1 more Smart Citation
“…More generally, the predictions of these properties must be robust in order to relate mass concentrations to size distributions of ambient aerosols and to calculate the radiative impacts of atmospheric aerosols. 45,46 Thus, a rigorous assessment of estimation methods based on solutions of known properties is of considerable value.…”
Section: Extension and Validation Of The Molar Refraction Mixing Rulementioning
confidence: 99%
“…The potential interplay of the resulting uncertainties in representing the degree of hygroscopic growth, the RH dependence of the refractive index, and the impact on optical growth factor must be more fully explored to better quantify uncertainties in radiative forcing efficiency. 46 In addition to examining the agreement of the mixing rules for κ, UManSysProp has been used to predict the hygroscopicity parameter κ as a function of water activity, shown in Figure 7(a). 43 For every mixture considered in this work, UManSysProp overpredicts the hygroscopic response (solid lines in Figure 6(a)).…”
Section: Comparison Of the Measured Hygroscopic Response With Predictmentioning
confidence: 99%
“…The SP2 is a widely used instrument that can measure the optical properties of every single particle. The measurement principle and instrumental setup of the SP2 have been discussed in detail previously (Stephens et al, 2003;Schwarz et al, 2006) and will be briefly described here. When the sample aerosol particles pass through the continuous Nd:YAG laser beam at 1064 nm with the circulating power of about 1 mW cm −2 in the cavity, eight sensors distributed at four directions synchronously detect the emitted or scattered light by using an avalanche photodetector (APD) at different angles (45 and 135 • ).…”
Section: Sp2mentioning
confidence: 99%
“…Moise et al (2015) estimated that the RF would increase by 12 % if the RRI varies from 1.4 to 1.5. Valenzuela et al (2018) reported that the uncertainties in RF are estimated to be 7 % when the aerosol RRI varies by 0.1. Therefore, it is pressing that the uncertainties of the RI be reduced when estimating the RF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation